PAROTID GLAND VENOLYMPHATIC MALFORMATION PRESENTATION AS MACROGLOSSIA - Kazmi, Nafeesa Batool; Sajjad, Kumail; Waqar, Fouzia; Khan, Saqib U; Ghafar, Abdul (Journal of Ayub Medical College Abbottabad, 2020)
Venolymphatic malformations (VLM) are the rare congenital disorders but the parotid gland VLMs are the rarest. Most of the parotid lesions present with unilateral swellings. Aetiology is unknown. Interestingly, this case came in OPD with the macroglossia and only complaint was cosmetic problem. Diagnosis was confirmed on the basis of Magnetic resonance imaging which is gold standard. Doppler ultrasonography showed low flow. Intra lesion electro cautery was done. There is need to focus on malformations and work to find out the causes. Keywords: Venolymphtic malformation; Parotid gland Venolymphatic malformation; Marcoglossia; Parotid Gland